Structure elucidation of beta-cyclodextrin-xylazine complex by a combination of quantitative H-1-H-1 ROESY and molecular dynamics studies - Ali, Syed Mashhood; Fatma, Kehkeshan; Dhokale, Snehal A. (Beilstein Journal of Organic Chemistry, 2013)
The complexation of xylazine with beta-cyclodextrin was studied in aqueous medium. H-1 NMR titrations confirmed the formation of a 1:1 inclusion complex. A ROESY spectrum was recorded with long mixing time which contained TOCSY artifacts. It only confirmed the presence of xylazine aromatic ring in the beta-cyclodextrin cavity. No information regarding the mode of penetration, from the wide or narrow side, could be obtained. We calculated the peak intensity ratio from the inter-proton distances for the most stable conformations obtained by molecular dynamics studies in vacuum. The results show that highly accurate structural information can be deduced efficiently by the combined use of quantitative ROESY and molecular dynamics analysis. On the other hand, a ROESY spectrum with no spin diffusion can only compliment an averaged ensemble conformation obtained by molecular dynamics which is generally considered ambiguous.
Keywords: beta-cyclodextrin; inclusion complex; ROESY; simulation studies; xylazine

Sugar furanoid trans-vicinal diacid as a gamma-turn inducer: synthesis and conformational study - Vangala, Madhuri; Dhokale, Snehal A.; Gawade, Rupesh L.; Pattuparambil, Rajamohanan R.; Puranik, Vedavati G.; Dhavale, Dilip D. (Organic & Biomolecular Chemistry, 2013)
A simple method for the synthesis of a sugar furanoid trans vicinal diacid and its incorporation into the N-terminal tetrapeptide sequence (H-Phe-Trp-Lys-Thr-OH) to get glycopeptide 8 has been described. 2D NMR and MD simulation studies of 8 clearly show that the sugar diacid adopts a gamma-turn conformation towards the N-terminus.

Switching the H-bonding network of a foldamer by modulating the backbone chirality and constitutional ratio of amino acids - Ramesh, Veera V. E.; Vijayadas, Kuruppanthara N.; Dhokale, Snehal A.; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2013)
This communication describes the folding propensity of a hetero-foldamer motif featuring proline (Pro) and anthranilic acid (Ant) residues in a 1:2:1 (alpha: beta: alpha) constitutional ratio. Structural investigations unequivocally suggest that the hydrogen-bonding network of this foldamer motif can be switched between 9-membered and 6-membered by modulating the backbone chirality and constitutional ratio of the amino acid residues.